Metabolic rate in febrile infants. Issue 3 (March 1996) - McIntyre, J; Hull, D
Abstract : An open circuit indirect calorimeter was used to measure resting energy expenditure in febrile infants. Twelve infants admitted to hospital with fever (axillary temperature 37.5 degrees C) were studied on admission and then again at the same time of day and in similar environmental conditions after the fever had resolved. Mean age of the infants was 0.31 years (range 0.12-0.54) and the mean body weight 6.59 kg (range 4.50-8.88 kg). On average the infants' axillary temperatures were +2.1 degrees C higher when they were febrile. Overall the mean difference in oxygen consumption (VO2), carbon dioxide production (VCO2), and resting energy expenditure (REE) between the febrile and afebrile measurements was not statistically significant. Of eight infants with a greater REE when febrile, five were diagnosed as having viral illness and three had bacterial meningitis. Of the four with a lower REE when febrile, two had viral illness and two had bacterial infection (one chest infection and one meningitis). In conclusion, there was no consistent alteration of REE during a fever in infants 1 to 6 months of age. In particular, age and type of infection were not predictors of whether REE would increase or decrease during the illness.